2017
DOI: 10.5935/medicalexpress.2017.05.03
|View full text |Cite
|
Sign up to set email alerts
|

Patients with chronic high spinal cord injury can be safely treated with neuromuscular electrical stimulation: cardiovascular function is unaffected

Abstract: OBJECTIVE:To identify changes in blood pressure and heart rate in individuals with chronic paraplegia undergone neuromuscular electrical stimulation treatment. METHOD: Design: Observational prospective. Participants: Twenty individuals with chronic paraplegia (neurological level above T6) belonging to two different groups (G1 and G2) were submitted to an upper limb exercise test. G1 patients (n=13) had been treated with neuromuscular electrical stimulation (25Hz, pulses of 300μs, 100V) for 2 years or more, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Recently, it has been shown that persons with SCI above or at T6 can be safely treated with NMES to manage variations in BP [25]. Twenty participants with chronic paraplegia were divided into two groups (G1 and G2) and subjected to an upper limb exercise test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that persons with SCI above or at T6 can be safely treated with NMES to manage variations in BP [25]. Twenty participants with chronic paraplegia were divided into two groups (G1 and G2) and subjected to an upper limb exercise test.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty participants with chronic paraplegia were divided into two groups (G1 and G2) and subjected to an upper limb exercise test. The G1 (T2-T6, n = 13) participants were treated with NMES for 2 years or more, at least once a week and G2 (T3-T5, n = 7) participants did not receive NMES training [25]. No differences were noted in BP during upper limb exercise test in any of groups.…”
Section: Discussionmentioning
confidence: 99%